Combined Eccentric-Isokinetic and Isoinertial Training Leads to Large Ring-Specific Strength Gains in Elite Gymnasts - Christoph Schärer (Sports, 2022)
In male elite gymnastics, lately, eccentric training is often used to improve the maximum specific strength of static elements on rings. Therefore, in this study, we aimed to investigate the effects of a three-week, gymnastic-specific, eccentric-isokinetic (0.1 m/s) cluster training with a change of stimulus after three of six training sessions (eccentric-isokinetic with additional load) on a computer-controlled training device on the improvement of the elements swallow and support scale on rings. Maximum strength and strength endurance in maintaining the static positions of ten international elite male gymnasts were determined on a weekly basis. After three weeks of training, specific maximum strength and strength endurance increased significantly (strength: swallow: +8.72%, p < 0.001; support scale: 8.32%, p < 0.0001; strength endurance: swallow: +122.36%; p = 0.02; Support Scale: +93.30%; p = 0.03). Consequently, top gymnasts can considerably improve ring-specific strength and strength endurance in only three weeks. The separate analysis of the effects of both eccentric-isokinetic training modalities showed that efficiency might even be increased in future training interventions. We suggest using this type of training in phases in which the technical training load is low and monitoring the adaptations in order to compile an individually optimized training after an intervention.